Ethical governance and society - Chatterjee, Tishyarakshit (2013)
Ethical governance provides freedom to society and individuals within to attain their best selves. The bottom-up heterogeneity of governance will throw up its own common links, codes of behaviour, transactions, economic and social relations as the basis for ethical governance in society to take form in total sync with the norms of extant society. Therefore, our ethical vision must ultimately promite a ground swell of support for a government structure that reflects society in all its vertical and horizontal heterogeneity. To this end an approach spearheading social sector reforms and empowerment of human resources is needed. Such a strategy will involve knowledge development from research, knowledge processing and knowledge sharing in all areas of governance and social sector reforms. - Reproduced.
Keywords: Public administration